2017
DOI: 10.1371/journal.pmed.1002395
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease concordance within Indian households: A cross-sectional study

Abstract: BackgroundThe household is a potentially important but understudied unit of analysis and intervention in chronic disease research. We sought to estimate the association between living with someone with a chronic condition and one’s own chronic condition status.Methods and findingsWe conducted a cross-sectional analysis of population-based household- and individual-level data collected in 4 socioculturally and geographically diverse settings across rural and urban India in 2013 and 2014. Of 10,703 adults ages 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 40 publications
(63 reference statements)
3
38
1
4
Order By: Relevance
“…The much lower number of individuals with new type 2 diabetes in the Framingham cohort [20] and in our own study (both n < 770) may partly explain why neither was able to replicate the findings from the much larger Swedish and US studies [19,26]. In addition, however, cross-sectional studies have reported inconsistent findings with respect to the statistical significance of the risk of type 2 diabetes among individuals whose spouses have the disease [15,16,27,28].…”
Section: Discussioncontrasting
confidence: 69%
“…The much lower number of individuals with new type 2 diabetes in the Framingham cohort [20] and in our own study (both n < 770) may partly explain why neither was able to replicate the findings from the much larger Swedish and US studies [19,26]. In addition, however, cross-sectional studies have reported inconsistent findings with respect to the statistical significance of the risk of type 2 diabetes among individuals whose spouses have the disease [15,16,27,28].…”
Section: Discussioncontrasting
confidence: 69%
“…There is also a paucity of evidence about how clusters of conditions develop and change over time, meaning it can be difficult to predict how the disease burden might change over the course of a patient's life, and difficult to identify when interventions might be best applied. 146 Additionally, it has been established that certain chronic conditions tend to cluster in families and communities, 147,148 but it remains uncertain whether multimorbidity per se also clusters in this way.…”
Section: Clusters Of Conditionsmentioning
confidence: 99%
“…However, there is also growing evidence to suggest that factors that operate at the household level can also be drivers of disease risk -individuals who live with people with a chronic physical or mental health condition have been found to be at an increased risk of experiencing the same condition themselves, in both HICs 397, 398,399 and LMICs. 400 Although living with others and having a large social network may be protective for multimorbidity (as noted in Section 3.2.2), it will be valuable to consider whether factors that operate at the household level can also influence multimorbidity clusters in a similar manner as to single conditions.…”
Section: Determinants Of Clusters Of Conditionsmentioning
confidence: 99%
“…Cobb et al [2] suggest that an individual has almost double the risk of becoming obese if their spouse becomes obese. From a cross-sectional perspective, Patel et al [14] suggest that obesity is associated with spousal diabetes status. We extend these observations using longitudinal data on age-related obesity trajectories by spousal diabetes status.…”
Section: Discussionmentioning
confidence: 99%